Characterization of phenotypic and genotypic diversity in subclones derived from a clonal cell line. (11th August 2018) - Tharmalingam, Tharmala; Barkhordarian, Hedieh; Tejeda, Nicole; Daris, Kristi; Yaghmour, Sam; Yam, Pheng; Lu, Fang; Goudar, Chetan; Munro, Trent; Stevens, Jennitte
Abstract : Regulatory guidelines require the sponsors to provide assurance of clonality of the production cell line, and when such evidence is not available, additional studies are typically required to further ensure consistent long‐term manufacturing of the product. One potential approach to provide such assurance of clonal derivation of a production cell line is to characterize subclones generated from the original cell line and assess their phenotypic and genotypic similarity with the hypothesis that cell lines derived from a clonal bank will share performance, productivity and product quality characteristics. In this study, a production cell line that was cloned by a validated FACS approach coupled with day 0 imaging for verification of single‐cell deposition was subcloned using validated FACS and imaging methods. A total of 46 subclones were analyzed for growth, productivity, product quality, copy number, and integration site analysis. Significant diversity in cell growth, protein productivity, product quality attributes, and copy number was observed between the subclones, despite stability of the parent clone over time. The diversity in protein productivity and quality of the subclones were reproduced across time and production scales, suggesting that the resulting population post sub‐cloning originating from a single cell is stable but with unique properties. Overall, this work demonstrates that the characteristics of isolated subclones are not predictive of a clonally derived parental clone. Consequently, the analysis of subclones may not be an effective approach to demonstrate clonal origin of a cell bank. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 34:613–623, 2018